2006
DOI: 10.1093/ajcn/83.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones modulate immune function in healthy postmenopausal women

Abstract: Soymilk and supplemental isoflavones modulate B cell populations and appear to be protective against DNA damage in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 37 publications
5
122
0
2
Order By: Relevance
“…Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) . When pure molecules were utilized, CRP and IL-8 were lowered by quercetin supplementation in runners (64) and bikers (65) , while quercetin plasma levels increased.…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 78%
See 1 more Smart Citation
“…Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) . When pure molecules were utilized, CRP and IL-8 were lowered by quercetin supplementation in runners (64) and bikers (65) , while quercetin plasma levels increased.…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 78%
“…Long-term intervention studies conducted using soya as a source of bioactive molecules showed reduction in levels of vascular cell adhesion molecule-1 and CRP (59,60) , but also a lack of effect on CRP (61)(62)(63) , TNFa (61,63) and IL-6 (60,62) . Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%
“…Soy isoflavones, acting as phytoestrogens, may have a positive effect on muscle mass because of their affinity for estrogen receptor-␣, which is found on muscle [21], or may exert their effects on reducing inflammation [22][23][24] associated with muscle protein degradation [25][26][27][28]. Besides soy isoflavones, other soy constituents such as protein may affect muscle mass [29].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these processing effects are relevant to humans is unknown, but there is certainly considerable reason for doubt. In humans, isoflavone pharmacokinetics appears to be similar in response to the consumption of soy foods and isoflavone supplements (116), and, with the exception of cholesterol reduction, the limited number of direct comparisons has shown similar effects of supplements and soy foods on health outcomes (117).…”
Section: Are Isoflavones Contraindicated For Some Women?mentioning
confidence: 99%